TERAPI AKTIVITAS KELOMPOK BERMAIN ESTAFET BOLA - Siti Robeatul Adawiyah; Mohamad Nanda Saputra Junaedi; Lilis Rusfitasari; Sumiatun Sumiatun; Lingling Rahmawati; Siti Homalia; Arum Arofiyah Wiharti; Esti Widiyawati; Nadilah Rahmawati; Rahmah Nurazizah; Andini Andini; Ahmad Fujiyanto (Journal of Educational Innovation and Public Health, 2023)
Elderly is someone who is over 65 years old and the elderly are also a risk group whose population is increasing. Elderly is not a disease, but an advanced stage of a life process which is marked by a decrease in the body's ability to adapt to environmental stress. The purpose of doing perceptual stimulation group activity therapy is that the client can reduce the depression he is experiencing and follow the treatment program optimally. Health counseling was held on Wednesday, June 7 2023. The population in this counseling were officers and the elderly in the Wisma Durian Room Tresna Werdha Budi Mulia 2 Social Institution. After carrying out group activity therapy "ball relay" the results (100%) were officers and the elderly understand, understand and be able to exemplify how to play the ball relay.